Explaining turn of the year order flow imbalance - Chelley-Steeley, Patrìcia Lorraine; Lambertides, Neophytos; Steeley, James M. (My University, 2016)
The paper provides evidence of a turn of the year effect in the order flow imbalance of both retail and institutional investors. In December there is net selling pressure which is reversed in January. We examine high frequency intraday order flow information and find that the changes in order flow imbalance between December and January are related to firm risk factors and characteristics. We find that retail order flow imbalances are associated with a wide range of risk characteristics including beta, illiquidity and unsystematic risk. Imbalances in institutional order flow are associated with only a small number of risk variables. We show that these order flow changes are important because risk premiums are elevated in January. Our results are robust to the effects of decimalization.
Keywords: Order flow imbalance; Risk; Turn of the year